PANJI MASK: EVERYTHING IN THE ENTIRE ELEMENTS OF CULTURE - Aditya Candra Kartika (Universitas Sebelas Maret, 2017)
This paper aims to discuss and describe the study of Panji Mask in Koentjaraningrat cultural elements. The data source can be from mask crafters, observations and literature studies. Data analysis using qualitative descriptive analysis technique. The results of this study is a description of the toopeng and its role in every element of culture that includes; (1) religion; (2) system of social organization; (3) economic systems and livelihoods; (4) knowledge systems; (5) language; (6) art; and (7) living equipment and technology systems.